Scholarly Discussion of Infanticide? - Garasic, MirkO D. (The Hastings Center report, 2012)
I feel the urge to express my solidarity with Alberto Giubilini and Francesca Minerva, the authors of the much-discussed article “After-Birth Abortion: Why Should the Baby Live?” that appeared in the Journal of Medical Ethics in February. Both their argument and, more sadly, they themselves suffered a violent attack by people who obviously do not consider freedom of expression an important value. Censorship does not fit well with the mission of scholarship—particularly when the scholarship depends on a method of speculation and hypothetical argument, as in the case of philosophy and bioethics—and the level of hatred and extremism expressed about the article seem out of proportion. Having said this, though, I want to consider why publishing the article was nonetheless inappropriate.